Durability analysis of rotary direct drive electro-hydraulic pressure servo valve based on failure physics principle. - Jianrui Zhang; Xing Wei; Ni Li; Xiaonan Pan; Yitong Sun (PLoS ONE)
The rotary direct drive electro-hydraulic servo valve (RDDPV) is extensively employed in hydraulic systems across aerospace, automotive, and various industrial sectors owing to its remarkable precision and rapid response characteristics. The investigation of the durability life of such devices, constituting intricate amalgamations of mechanical, electrical, and hydraulic components, has perennially posed a formidable challenge. To address this challenge, our study proposes a methodology grounded in failure mechanisms to systematically quantify the durability life of RDDPV. In conjunction with finite element analysis, this study delves into the fatigue durability of the transmission mechanism and the wear durability of the slide valve-two components recognized as vulnerabilities within the RDDPV. Initially, a novel approach is proposed that integrates probability theory and fuzzy theory with the traditional Miner theory, enhancing the accuracy of fatigue life predictions for transmission mechanisms. Subsequently, a meticulous examination of the wear mechanism of the slide valve ensued, wherein we quantitatively characterized the radial wear between the valve core and sleeve using the degree of line wear. Ultimately, employing durability index calculations, the total operational life of the valve is ascertained at about 435,000 hours, thereby aligning with national standards. This research methodology not only contributes significantly to the field but also holds substantial reference value for the precise quantification of the durability life of analogous electro-hydraulic pressure servo valves.